Comparison of selection criteria for pre-weaning growth traits of Nelore cattle - Pena, CDO; Carvalheiro, R.; de Queiroz, S. A.; Fries, L. A. (Elsevier B.V., 2004)
Genetic parameters were estimated for pre-weaning average daily gain (ADG) and number of days to gain 160 kg from birth to weaning (D 160) of Nelore cattle. Ranks of animals were compared for these traits. Heritability estimates were 0.17 and 0.10 for ADG (direct and maternal), and 0.14 and 0.09, for D 160 (direct and maternal). Rank correlations between expected breeding values (EBV) were 0.97 and 0.95, for direct and maternal effects, respectively. Despite similar heritability estimates and high rank correlations, results showed that changes in rank could happen when choosing the best animals according to EBV for D 160 or ADG. There were evidences that sires selected using D 160 would produce progeny that achieve a specified market weight at an earlier age and would be more uniform, since this criterion is calculated as a harmonic mean function. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: average daily gain; Beef cattle; days to gain 160 kg from birth to weaning; harmonic mean; Heritability